(untitled) (Economia Aplicada, 2005)
This paper deals with a problem observed in federal fiscal relations: the capture of transfers received by local interest groups. Four hypotheses established in the literature are tested: capture is expected to increase with fiscal illusion, low bargaining power of the voter, over-financing of some local governments, and degree of poverty. The empirical tests use data from Brazilian local governments. The econometric results are coherent with the hypotheses and give hints on how to prevent capture when designing an intergovernmental transfer system.